Why Should Women Cover Their Heads Because of the Angels? (1 Corinthians 11:10) - Stuckenbruck, Loren T. (Stone-Campbell journal, 2001)
In 1 Cor 11:2-16 Paul negotiates between theological ideals (11:11- 12) and his assumptions about the sexuality of men, women, and angels. Pauls instructions derive from what he assumes is proper to the ordering of the cosmos. It is therefore less important to decide whether in 11:10 Paul is concerned with good or bad angels.